Data from: Diel movement patterns influence daily variation in wolf kill rates on moose - Vander Vennen, Lucas M.; Patterson, Brent R.; Rodgers, Arthur R.; Moffatt, Scott; Anderson, Morgan L.; Fryxell, John M. (Zenodo, 2016)
Variation in predation can have important consequences for predators and prey, but little is known about associated mechanisms. Diel interactions between predators and prey are commonly assumed to be influenced by movement speeds of both predators and prey individuals, sensu the ideal gas model, but the influencing factors of diel predation dynamics have yet to be empirically examined. In this study, we apply principles of the ideal gas model to predict diel variation in kill frequency of moose (Alces alces) by wolves (Canis lupus) in northern Ontario, Canada based on GPS radio-telemetry data combined with field verification of kills. We used GPS telemetry data from wolves and moose combined with a unique data set on the diel pattern of wolf kills to test whether predator movement rate, prey movement rate, and ambient light condition influence diel variation in kill rates of wolves on moose. Our results indicate that the kill rate between wolves and moose was principally related to the effective movement rate of predators and prey, as predicted by the ideal gas model. We found little evidence that light conditions had any effect on kill rates, but rather the majority of kill rate variation corresponded to wolf movement rate, which was over an order of magnitude higher than that of moose. Diel factors of wolf and moose kill rates Wolf and moose movement rate data collected from GPS collared animals in northern Ontario, and represent population-level average movement rate during each of the 16 time bins throughout the 24-hour cycle. Kill rate is the distribution throughout the 16 time bins of the time of kill from field-verified sites of wolves predating on moose. Crepuscular light conditions were calculated as the average proportion of a twilight period within each time bin, and total light conditions were calculated from a crude model assuming 0 for night, 0.5 for twilight, and 1 for daylight. VanderVennen_etal_WolfMooseKillRates.csv